Violence in Rural Regions: the Case of Modern Turkey - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
The violence encountered on the countryside in Turkey is different from its counterpart in metropolitan areas by nature and this is only expected. Matters of honor regarding chastity, dispute over land, personal conflict and enmity leading to a crime or fights among children drifting along adults or trouble befalling close kin or friends and quickly encompassing those feeling responsible for them are the most frequently encountered forms of infringing the penal law. Some cultural traits also pave the way to possible violence easily. Personal memories are made use of in the article.
Keywords: Violence; crime; rural; cultural